SOSIALISASI RUMAH SEHAT DI KELURAHAN PURWOSARI KECAMATAN MIJEN - SEMARANG - Asri Nurdiana (Sekolah Vokasi Universitas Diponegoro, 2025)
Healthy homes are a concept of housing as a factor that can improve the health standards of its residents. Thus, it can be said that a healthy house is a building for shelter and rest as well as a means of family development that fosters a healthy life physically, mentally and socially, so that all family members can work productively. Therefore, the existence of healthy, safe, harmonious, orderly housing is very necessary so that the function and use of the house can be fulfilled properly.